Visualisasi Karakter Pramodawardhani dengan Pendekatan Fiksi Sejarah - CM, Noor Latif (Bina Nusantara University, 2013)
The figure of Pramodawardhani is a key figure in the history of Indonesia on the eighth century in Java. With these considerations, efforts to revive the character of Pramodawardhani are to contribute to the enrichment of Indonesian visual reference. At least, relics of artifacts at the time made the history of classical Indonesia experience confusion on trace of the story and visualization of its history. Visual reconstruction effort with fictional approach is way out to realize the data fragments both verbal and visual in visual understanding of the past with contemporary social norms perspective. Attributes that carried Pramodawardhani as being aristocratic Javanese classical land become static character without the frenzied of his supernatural power wrapping as a superhero. The fiction building which legally understands the metaphoric fact into an understanding of the modern imagination is the arena of visual reconstruction in some cases ever. Partial understanding of the history of Indonesia’s visual reference product presented by social media has been widely biased in visual building physically. The main cause boils down to the lack of fundamental studies in visual reconstruction pattern which is too premature to conduct the studies.